Two donor–acceptor (D–A) type Zn(ii) complexes as fluorescent probes for highly selective detection of iodide. Issue 11 (28th February 2020) - Su, Hao; Hao, Liang; Hussain, Wajid; Li, Zhongkui; Li, Hui
Abstract : Two noval donor-acceptor (D–A) type Zn(ii ) complexes ([Zn2 (L 1 )2 (MeCN)(MeOH)]·(MeCN) (1 ) and [ZnL 2 (H2 O)] (2 )) were obtained and selectively detected iodide as fluorescent probes. Abstract : Two D–A type Zn(ii ) coordination complexes ([Zn2 (L 1 )2 (MeCN)(MeOH)]·(MeCN) (1 ) and [ZnL 2 (H2 O)] (2 )) were synthesized from diaminomaleonitrile-based (DMN) Schiff-base ligands (L 1 = 2-amino-3-[(2-hydroxynaphthalen-1-ylmethylene)-amino]-but-2-enedinitrile, L 2 = 2-[(4-chloro-2-hydroxybenzylidene)-amino]-3-[(2-hydroxynaphthalen-1-ylmethylene)-amino]-but-2-enedinitrile). Based on the weak blue fluorescence in THF solution and the bright yellow fluorescence in the solid state, the ligand L 1 shows obvious aggregation induced emission (AIE) in a THF–H2 O solvent system. The fluorescence emission of complexes 1 and 2 exhibits a significant red-shift relative to that of the ligand in THF solution. Interestingly, because of aggregation caused by the interaction between L 1 and iodide (I − ), complexes 1 and 2 exhibit excellent selectivity for fluorescence detecting iodide, and the quenching efficiency of 2 with iodide is higher than that of 1 .